The Crusades in Arab school textbooks - Determann, Jörg Matthias (Islam and Christian-Muslim relations, 2008)
This article examines the depiction of the Crusades in Arab school textbooks. In the introductory first part, perceptions of the Crusades manifest in Arab historiography are described. In addition, modern political discourses referring to the Crusades among Arab authors, politicians and representatives of political Islam are explained. In the second part, accounts of the Crusades in school textbooks from Saudi Arabia, Jordan, Syria, Lebanon, Palestine, Egypt, Libya and Tunisia are analysed, focusing on the sources used by the books' authors, the terminologies, conceptions, reasoning, and narratives found in them, and the results of the Crusades as they are portrayed. The third part concludes by explaining three different approaches to how the textbooks relate the history, and shows the historical sensibilities concerning the Crusades as taught by the schoolbooks.